Spatial and non-spatial databases enhancement for hydrological information system (HIS) - Daman, Daut (Faculty of Computer Science and Information System, 2002)
In general, Geographical Information System (GIS) has four main components, namely data input, data model, data analysis and manipulation, and data presentation. These components are vital in order to make a GIS fully functional. This report is centered upon the research activities of selecting, synthesis, designing and implementing the data model components. The primary research issue is to develop a data model that have the capability of storing and managing changes in geographic features. A new perspective approach on the current data modeling is proposed in order to alleviate the current issue plaguing the GIS data management. In developing this new perspective, the feature based approach and system cube method are synthesized to produce a new data model. Consequently, the combination of these approaches resulted in the design of Double Cube Data Model, which integrates temporal information of geographic features. The Double Cube Data Model has been implemented using relational database system. After extensive testing, the Double Cube Data Model performed admirably in managing the dynamic changes of geographic features. In conclusion, temporal information is the prime importance in managing geographic data. In this report, the researcher has proved that temporal information can be integrated into a single GIS data model.